(untitled) (Scientiae Studia, 2012)
Amongst the different factors associated with a paradigm shift, and hence with a chemical revolution, the least discussed is that involving the so-called exemplary experiments: radical changes in chemistry's methodology and empirical procedures. In the case of natural and empirical sciences such changes may lead to obtaining previously inaccessible experimental data, and ultimately to a new approach to concepts, theories and hypotheses, that becomes the triggering factor for a chemical "revolution", a new paradigm. Much more than a chemical revolution, we should consider a gradual chemical evolution. We chose three situations as "exemplary": the change of empirical procedures in pneumatic chemistry with the use of the pneumatic trough containing mercury; the introduction of solvent extraction in substitution to the pyrogenic method for the extraction of natural organic compounds; a new understanding of "chemical analysis" associated with the substitution of sample comparison by analytic decomposition.